Development and Pilot Testing of an Encounter Tool for Shared Decision Making About the Treatment of Graves' Disease - Brito, Juan P. (Thyroid, 2015)
Background: The best treatment option for patients with Graves' disease (GD) depends on each person's situation and how the differences between the treatment options matter to them in bringing resolution to their illness. The objective of this study was to develop and test an encounter decision tool (GD Choice) for patients and clinicians to engage in shared decision making about the treatment of GD. Methods: GD Choice was developed using an iterative process based on the principles of interaction design and participatory action research. To evaluate the impact of the tool, a controlled before–after study was conducted, assessing the use of GD Choice versus usual care (UC). Results: Sixty-eight patients were enrolled, 37 to UC and 31 to GD Choice. At baseline, the groups were similar. Treatment discussion length was similar in both arms. After their visit, patients in both groups had similar knowledge about the options, except for GD Choice patients knowing significantly more about the complications of treatment (correctly answered by 83% vs. 55%; p = 0.04). Compared with UC, patients in the GD Choice arm had greater involvement in decision making observed on video recordings of clinical encounters (mean OPTION scale score, 35% vs. 30%; p = 0.02), but reported similar levels of decisional comfort and participation in shared decision making. Conclusions: GD Choice increases engagement in the decision-making process and knowledge regarding intervention complications without increasing the length of consultation. These promising results support the conduct of a randomized trial of GD Choice versus UC in a large multicenter trial.